Mindfulness Meditation Group: Upaya Peningkatan Kualitas Hidup dan Kesejahteraan Psikologis Pada Lansia Penderita Diabetes - Qona'ah, Arina; Nursalam, Nursalam; Astutik, Erni; Alfaruq, Muhammad Fikri; Lutfandini, Cherlys Tin; Amelia, Vira (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Elderly with diabetes melitus have low levels of psychological well-being and quality of life. This community service aims to improve the psychological well-being and quality of life of elderly people with diabetes melitus through mindfulness meditation groups. This community service was placed in Sukolilo Village in collaboration with the Sukodadi Lamongan Health Center. This activity was attended by 32 elderly with diabetes melitus. Community service activities include forming mindfulness meditation groups, developing mindfulness meditation modules through Focus Group Discussions with health workers at the Sukodadi Health Center, training in mindfulness meditation, and activity evaluation. The evaluation was conducted using a questionnaire on psychological well-being, quality of life; physical and laboratory examinations. The mindfulness meditation group improved the psychological well-being and quality of life of the elderly. Mindfulness meditation plays an important role in creating peace of mind and helping patients channel energy in a positive direction so it can improve the psychological well-being and quality of life of the elderly with diabetes melitus. Mindfulness meditation can be done periodically. It can be used as part of a chronic disease management program.Keywords: mindfulness meditation; psychological well-being; quality of life; diabetes melitus; elderly Abstrak: Lansia dengan diabetes melitusmemiliki tingkat kesejahteraan psikologis dan kualitas hidup yang rendah. Pengabdian masyarakat ini bertujuan untuk meningkatkan kesejahteran psikologis dan kualitas hidup lansia penderita diabetes melitusmelalui mindfulness meditation group. Pengabdian masyarakat ini dilakukan di Desa Sukolilo bekerjasama dengan Puskesman Sukodadi Lamongan. Kegiatan ini diikuti oleh 32 lansia penderita diabetes melitus. Kegiatan pengabdian masyarakat meliputi pelatihan meditasi mindfulness dan evaluasi kegiatan dengan kuosioner kesejahteran psikologis, kualitas hidup; pemeriksaan fisik dan laboratorium. Mindfulness meditation group mampu meningkatkan kesejahteran psikologis dan kualitas hidup lansia. Meditasi mindfulness berperan penting dalam menciptakan ketenangan pikiran dan membantu pasien menyalurkan energi ke arah yang positif sehingga dapat meperbaiki kesejahteraan psikologis dan kualitas hidup lansia dengan diabetes melitus. Mindfulnes meditasi dapat dilakukan secara berkala dan dijadikan sebagai salah satu bagian program penanganan penyakit kronis.Kata kunci: mindfulness meditation; kesejahteraan psikologis; kualitas hidup; diabetes melitus; lansia